Sistem perpustakaan digital bersepadu: sub-sistem perolehan atas talian Perpustakaan Sultanah Zanariah - Talib, Anuar (2002)
Acquisition system is important in a library business process, whereby it manages the process of ordering materials and gives feedback to requestor. The existing system used by Acquisition Department of Perpustakaan Sultanah Zanariah gives many problem to the department especially in handling the order process which takes long period. This problem occurs because the existing system uses manual communication while sending order, purchase order and getting feedback from the Acqusition Department. The online acquisition system or called Acquisition Online System will be developed to offer online communications between the Acquisition Department, the requestors and the vendors which can improve the turn around time in the order process. The implementation of the new system requires the books data in a UniVerse database on Windows NT are copied into temporary database. The interface system needs to develop to handle this problem. Accessing to the UniVerse database is done through the client/server concepts using UniVerse ODBC which is supported in the UniVerse environment. PHP (Hypertext Preprocessor) is chosen as the corresponding tool because of its ability in web. In general, this system helps requestor to order books, vendor views their purchase order and Acquisition Department can handle ordering process easily and quickly.